Accumulation of sugars in the xylem apoplast observed under water stress conditions is controlled by xylem pH. (11th July 2016) - Secchi, Francesca; Zwieniecki, Maciej A.
Abstract: Severe water stress constrains, or even stops, water transport in the xylem due to embolism formation. Previously, the xylem of poplar trees was shown to respond to embolism formation by accumulating carbohydrates in the xylem apoplast and dropping xylem sap pH. We hypothesize that these two processes may be functionally linked as lower pH activates acidic invertases degrading sucrose and inducing accumulation of monosaccharides in xylem apoplast. Using a novel in vivo method to measure xylem apoplast pH, we show that pH drops from ~6.2 to ~5.6 in stems of severely stressed plants and rises following recovery of stem water status. We also show that in a lower pH environment, sugars are continuously accumulating in the xylem apoplast. Apoplastic carbohydrate accumulation was reduced significantly in the presence of a proton pump blocker (orthovanadate). These observations suggest that a balance in sugar concentrations exists between the xylem apoplast and symplast that can be controlled by xylem pH and sugar concentration. We conclude that lower pH is related to loss of xylem transport function, eventually resulting in accumulation of sugars that primes stems for recovery from embolism when water stress is relieved.